Increased size and relative abundance of migratory fishes observed near the Athabasca oil sands - Tim J. Arciszewski; Kelly R. Munkittrick; Bruce W. Kilgour; Heather M. Keith; Janice E. Linehan; Mark E. McMaster (Canadian Science Publishing, 2017)
Responses to chemical and physical stressors are commonly expected among organisms residing near the Athabasca oil sands. Physiological effects have been observed in fishes during field studies; but further effects associated with development are not clear or consistent among species. For instance, data from a fish fence in 2009 show declines in the relative abundances of some species, including Arctic grayling (Thymallus arcticus). In contrast, increases were seen in white sucker (Catostomus commersoni). This divergence suggests incomplete understanding of the status of fishes residing near the oil sands. However, an important challenge limiting understanding is the lack of reliable baseline or reference data. To overcome this challenge, we used iterative normal ranges and a historical data set (electrofishing surveys done from 1987 to 2014) to determine if changes have occurred in fishes captured in the lower Athabasca River. These analyses revealed clear increases in the lengths of white sucker and walleye (Sander vitreus) and their relative abundances during the spawning season. The occurrence of these changes may be associated with overwintering location, but reduced fishing pressure in Lake Athabasca, eutrophication, or a cumulative effect may explain the form of changes detected in this study.